Pinterest como interface cultural: de escavações a molduras - Grebin, Bárbara Zilda (Universidade do Vale do Rio dos Sinos, 2014)
The study aims, from a communicative and technocultural approach, to understand how the website Pinterest, based on the examination of its main operating logics, updates the concept of cultural interface coined by Manovich (2001). To develop this research problem, initially, it is carried out an explanation of the methodological approaches and procedures, inspired by an archaeological behave, followed by an overview of the interface concept through some conceptions around the term, until reaching the key concept of this dissertation, cultural interface. With this, it advances on the instrumentalization of the research, digging through images and identifying frames (Kilpp, 2010), followed by analysis of empirical material collected and grouped into three constellations named as HCI, plasticity and crossings between online cultural devices. The research concludes with two main movements, the first answering to the initial research question, it is realized a shift from the initial concept of cultural interface due to contexts arising from web 2.0, and the second bringing through a frame, a proposal of an analysis structure of online cultural devices.
Keywords: Metodologia das molduras; Arqueologia da mídia; Web 2.0; Interface cultural; Pinterest; Frames methodology; Media archaeology; Cultural interface; ACCNPQ::Ciências Sociais Aplicadas::Comunicação